ANALYSIS OF THE APPLICATION OF THE STATEMENT OF FINANCIAL ACCOUNTING STANDARDS (PSAK) 106 CONCERNING MUSYARAKAH FINANCING AT BANK BRI SYARIAH BRANCH OFFICE BANDUNG CITARUM - Dimas Hardiansyah; In’amul Aufa (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2023)
AbstractThis study aims to determine the suitability of applying accounting treatment regarding the recognition, measurement, presentation, and disclosure of financial statements of musyarakah financing transactions with PSAK No. 106 at BRI Syariah Branch Office Bandung Citarum in 2019. This research is a field study with a qualitative approach. The subject of research is at BRI Syariah Branch Office Bandung Citarum. In contrast, the object of research is the recognition, measurement, presentation, and disclosure of financial statements of musyarakah financing transactions in 2019. Data collection techniques in research using interviews and documentation. The results of this study show that : (1) the recognition of musyarakah financing accounting is not entirely by PSAK No. 106 because profit sharing income is calculated based on projections and losses due to accidents are the responsibility of customers,  with discounts given; (2) accounting measurement of musyarakah financing by PSAK No. 106; (3) the presentation of musyarakah financing accounting is not by PSAK No. 106 because the cash handed over to customers is presented as musyarakah financing: (4) the disclosure of musyarakah financing accounting is not by PSAK No. 106 because BRI Syariah Branch Office Bandung Citarum does not make notes to the financial statements.Keywords: Musyarakah Financing, Statement of Financial Accounting Standards (PSAK) No. 1